A new species of freshwater turtle of the genus Elseya (Testudinata: Pleurodira: Chelidae) from the Northern Territory of Australia - Thomson, Scott; Georges, Arthur (Zootaxa, 2016)
The genus Elseya has had a checkered taxonomic history, but is now restricted to species characterized by an alveolar ridge on the triturating surfaces of the jaw. The Australian forms were once regarded as a single widespread species extending from the Mary River of south-eastern Queensland to the Fitzroy River of north Western Australia, but a number of Australian species have now been identified based on a combination of molecular and morphological data—Elseya dentata, E. irwini, E. lavarackorum and E. albagula. The genus is represented in New Guinea by E. branderhorsti, E. novaeguineae, E. schultzii, and E. rhodini. One additional Australian taxon first identified in 1981 and subsequently established as a distinct taxon by molecular studies, is described here. It is a large chelid turtle that can be distinguished from all other Australian members of the genus Elseya by the distinctive cream or yellow plastron, free of the dark streaking, blotches or suffusing present in other species; an extensive bridge with little or no abrupt angle between the bridge and the ventral surface of the plastron; a head shield broken into a series of small plates rather than a single unit; flat uncornified temporal scales; and a narrower, less robust skull. Osteologically, it can be distinguished from Elseya dentata by the contact of the vomer and the pterygoids. The carapace is typically a light to medium brown in color whereas the carapace of Elseya dentata is typically dark brown to almost black in color. Distribution is the Mary, South Alligator, East Alligator, Goyder and Mann River drainages of the north east of the Northern Territory, Australia. It does not appear to be in sympatry with any other member of Elseya. It is, however, in sympatry with three species of Chelodina, at least two species of Emydura, Myuchelys latisternum and Carettochelys insculpta.